Perception, acceptability and challenges of digital adherence technology among TB healthcare workers - I. Gordon; B. Odume; C. Ogbudebe; O. Chukwuogo; N. Nwokoye; S. Useni; E. Efo; M. Gidado; E. Aniwada; A. Ihesie; D. Nongo; R. Eneogu; et al. (The Union, 2024)
INTRODUCTION: Successful treatment of TB requires high levels of adherence to treatment. This has been found to be below optimal with directly observed therapy (DOT), and digital adherence technologies (DATs) offer a promising approach to non-adherence to medication and improving treatment outcomes. This study explores the perception, acceptability, and challenges of DATs among healthcare workers (HCWs). METHODS: The study was conducted in eight states in Nigeria among Health Care workers involved in treating patients with TB. This was a descriptive cross-sectional study using an open questionnaire and analysed using IBM SPSS v25. RESULTS: Twenty-three HCWs (95.8%) agreed that DATs helped them provide better support and counselling to their patients. All of them would recommend DATs to their patients and found it easy to explain them. Eleven (45.8%) of them were not able to use DATs on a few occasions; their reasons were poor network (n = 9, 37.5%) and (n = 1, 4.2%) power failure. CONCLUSION: DATs help HCWs provide better support and care regarding real-time tracking of their patients' adherence to treatment and possibly reduction of attrition. This implies that DATs are a suitable alternative to DOT to help HCWs provide the best care and support to their patients towards achieving the End TB targets.